Morphological and electrical properties of Nickel based Ohmic contacts formed by laser annealing process on n-type 4H-SiC. (July 2019) - Rascunà, S.; Badalà, P.; Tringali, C.; Bongiorno, C.; Smecca, E.; Alberti, A.; Di Franco, S.; Giannazzo, F.; Greco, G.; Roccaforte, F.; Saggio, M.
Abstract: This work reports on the morphological and electrical properties of Ni-based back-side Ohmic contacts formed by laser annealing process for SiC power diodes. Nickel films, 100 nm thick, have been sputtered on the back-side of heavily doped 110 µm 4H-SiC thinned substrates after mechanical grinding. Then, to achieve Ohmic behavior, the metal films have been irradiated with an UV excimer laser with a wavelength of 310 nm, an energy density of 4.7 J/cm 2 and pulse duration of 160 ns. The morphological and structural properties of the samples were analyzed by means of different techniques. Nanoscale electrical analyses by conductive Atomic Force Microscopy (C-AFM) allowed correlating the morphology of the annealed metal films with their local electrical properties. Ohmic behavior of the contacts fabricated by laser annealing have been investigated and compared with the standard Rapid Thermal Annealing (RTA) process. Finally, it was integrated in the fabrication of 650V SiC Schottky diodes.